Expression of fibroblast growth factor 22 (FGF22) and its receptor, FGFR1B, during development and regression of bovine corpus luteum - Castilho, A. C. S. (2019)
The aim of this study was to determine the expression of fibroblast growth factor 22 (FGF22) in the bovine corpus luteum (CL) and to investigate the effects of in vivo total or partial cloprostenol-induced luteolysis on the mRNA abundance of FGF22 and its receptor, FGFR1B. Corpora lutea at different stages of development were then dissected from abattoir ovaries (n = 10/stage); a portion of the tissue samples was fixed in paraformaldehyde and the remaining samples were homogenized and subjected to total RNA extraction. To assess mRNA abundance of target genes during induced luteolysis, nineteen cows were synchronized and then randomly assigned to a Latin square design as follows: Control; 2 administrations of prostaglandin F-2 alpha (PGF(2 alpha), total luteolysis; 2 x 250 mu g of cloprostenol sodium) and 1/6PGF(2 alpha) (partial luteolysis; 83.33 mu g of cloprostenol sodium). FGF22 and FGFR1B expression levels were measured by RT-qPCR, and FGF22 protein expression was detected by immunohistochemistry. In summary, FGF22 mRNA was detected at all stages of CL development, and FGF22 protein was also detected in luteal tissue. FGF22 mRNA expression was lower at stage IV than at stage III (P < 0.05), and the same pattern was observed in luteal immunoreactivity. Furthermore, cloprostenol-induced luteolysis, both total and partial, increased FGFR1B mRNA abundance in luteal tissue (P < 0.05), but did not affect FGF22 mRNA abundance. In conclusion, these data suggest a potential role for the FGF22-FGFR1B system during development and regression of bovine CL. (C) 2018 Elsevier Inc. All rights reserved.